ASSISTÊNCIA DE SAÚDE ÀS MULHERES MUÇULMANAS NO BRASIL: UMA ANÁLISE DA RELAÇÃO ENTRE O SISTEMA RELIGIOSO ISLÂMICO E A POLÍTICA NACIONAL DE ATENÇÃO INTEGRAL À SAÚDE DA MULHER. - LIMA, KAYTE CHAVES OLIVEIRA DE (2016)
This dissertation aims to analyze the Islamic religious aspects and the implications of gender relations in Islam to the Muslin women healthcare, and, through it, discuss the importance for the healthcare providers having the previous knowledge of the cultural influence of Islamic faith and health related perceptions, so it can be proposed a health assistance congruent with these women, taking as reference the Brazilian Women’s Integrated Health Attention Policy. This research has a qualitative approach, with the development of a field research and applying a semi structured interview guide, with questions about Islam and women’s health. A total of ten interviews were conducted, those being: four women converted to Islam, three women from a Muslim family, two sheiks and one social assistant. The interviews were conducted at the Islam Divulgation Center to Latin America and Caribe (CDIAL) and at World Assembly of Muslin Youth in Latin America (WAMY)